Factors affecting the performance of Bumiputera SMEs in Melaka / Muhammad Azlan Zulkifli - Zulkifli, Muhammad Azlan (Faculty of Business and Management, 2015)
The purpose for this quantitative research is to study the factors that affect the performance of Small Medium Enterprises (SMEs) in Melaka. There were five variables used in this research to collect quantitative data from the subjects which were effective entrepreneurship, appropriate human resource, the use of marketing information, information technology and the performance of the company. The respondents of this study consist of bumiputera SMEs in Melaka. The data for this research were collected by questionnaires that given to the respondents. 140 questionnaires were distributed randomly to the entrepreneurs to identify whether there is a relationship between independent variables and dependent variable. Then, the data were analyzed using frequency analysis, reliability analysis, Pearson‟s Rank Correlation Coefficient and multiple linear regressions. Results of the study show that there is positive significance for the variables. The results also indicate that the use of marketing information and appropriate human resource are independent variables that contribute in SMEs performance in Melaka (β = 0.361, p = 0.000) and (β = 0.314, p = 0.003).